Outer-Convex Dominating Set in the Corona of Graphs as Encryption Key Generator. (26th October 2020) - Shao, Zehui; Kosari, S.; Anoos, R.; Sheikholeslami, S. M.; Dayap, J. A.
Abstract : In this paper, we present a new type of symmetric encryption by converting the classical monoalphabetic affine cipher into a polyalphabetic cipher. The proposed encryption utilizes the properties of outer-convex dominating set in the corona of graphs to generate random keys from the shared keyword to every character of the message. The new encryption eliminates the weaknesses of affine cipher, thus increasing the level of confidence for exchanging messages.